PENANGGUHAN PENAHANAN TERHADAP GISEL ANASTASIA DITINJAU DARI KITAB UNDANG HUKUM ACARA PIDANA DAN UNDANG-UNDANG TENTANG PORNOGRAFI - Muhammad Ikhwan Adabi; Chandra Darusman; Jalaluddin Jalaluddin; Adam Sani (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Suspension of detention is regulated in Article 31 of Law no. 8 of 1981 concerningCriminal Procedure Law, which states that at the request of a suspect or defendant,an investigator or public prosecutor or judge, in accordance with their respectiveauthority, can hold a suspension of detention with or without a guarantee of moneyor a guarantee of person, based on the conditions. which is determined. Theserequirements are regulated in Article 21 paragraph (1) of the Criminal ProcedureCode or referred to as subjective requirements and Article 21 paragraph (4) KUHAPor so-called objective requirements. The subjective view carried out by the PoldaMetro Jaya investigators in suspending detention of a case (GA) is not in accordanceor continuous with Article 21 paragraph (1) of the Criminal Procedure Codeaccording to the author's subjective view. Against (GA) is charged with Article 4paragraph (1) jo. Article 29 and / or Article 8 of Law no. 44 of 2008 concerningPornography. The criminal regulation that ensnares (GA) is in the form ofimprisonment for more than five years. If seen from the objective requirements, thisis not in accordance with Article 21 paragraph (4) of the Criminal Procedure Code.Article 21 paragraph (4) of the Criminal Procedure Code states that the conditions fordetention of a suspect or defendant cannot be withdrawn, the suspect's ordefendant's relationship with a prison sentence of more than five years